Pengaruh Leverage Ratio terhadap Return Saham pada Perusahaan Food and Beverages di Sumatera Utara yang Terdaftar di Bursa Efek Indonesia - Rizna Nur Ayyuna; Ihsan Effendi; Wan Rizca Amelia (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2021)
This study aims to determine the effect of the leverage ratio on stock returns in food and beverage companies listed on the Indonesia Stock Exchange. This type of research is explanatory research, namely research that explains the relationship between existing variables. The method used is multiple panel linear regression analysis with the help of the program eviews 10. The population in this study were all food and beverage companies listed on the Indonesia Stock Exchange in 2014-2018, amounting to 25 companies. The sample in this study were  4 companies. The results showed that based on the F test, debt to equity ratio, debt to asset ratio, long term debt to equity ratio had a probability value of 0.145266 0.05 and the Ftable value of 3.86 and the Fcount value of 2.306206, which means that Fcount Ftable simultaneous debt to equity ratio, debt to asset ratio, long term debt to equity ratio have no effect on stock returns. The coefficient of determination (R2) is 0.2462, so it can be concluded that 24.62% of stock returns are influenced by the debt to equity ratio, debt to asset ratio, and long term debt to equity ratio and the remaining 75.38% is influenced by other variables that are not in the this research.